Synthesis and characterization of Cu@Cu2O core shell nanoparticles prepared in seaweed Kappaphycus alvarezii media - Khanehzaei, Hajar; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Ajdari, Zahra (Electrochemical Science Group, 2014)
This study reports a synthesis of Cu@Cu2O core shell nanoparticles (NPs) in Kappaphycus alvarezii (K. alvarezii) media via a chemical reduction method. The nanoparticles were synthesis in an aqueous solution in presence of K. alvarezii as stabilizer and CuSO4.5H2O precursor. The synthesis proceeded with addition of NaOH as pH moderator, ascorbic acid as antioxidant and hydrazinium hydroxide as the reducing agent. The resulting nanoparticles characterized by using UV–vis spectrum, X-ray diffraction, Transmission electron microscopy, Fourier transform infrared (FT-IR) and atomic force absorption (AFM). The UV-visible spectra indicate to peaks at 590 nm and 390 which confirmed the formation of Cu@Cu2O-NPs. The XRD used in analysis of the crystal structure of nanoparticles. The morphology and structure of the K. alvarezii/Cu@Cu2O-NPs were investigated by TEM and AFM. The average size of Cu@Cu2O-NPs obtained were around 53nm that confirmed by using X-ray diffraction, TEM and AFM. The Fourier transform infrared FT-IR)spectrum suggested the complexation present between K. alvarezii and Cu@Cu2O-NPs.